Re-reading of the Concept of Naskh and Mansukh According to Nasr Hamid Abu Zaid and Its Implications for the Interpretation of the Qur’an - Muhammad Fajri; Suheri Suheri; Tarmizi Tarmizi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article discusses the reconstruction of one of the fundamental concepts in ‘ulumul Qur’an, namely the theory of nasikh-mansukh, which has long been regarded by some classical scholars as definitive and unchanging. One of the figures undertaking this reconstruction is Nasr Hamid Abu Zayd. Nasr Hamid’s reconstruction of the concept of nasikh-mansukh is a response to the ongoing debate between groups that accept and those that reject the existence of nasikh-mansukh in the Qur’an. According to Nasr Hamid, one of the factors causing this debate is the interpretation of naskh as the abrogation or cancellation of a verse. For Nasr Hamid, such a meaning fails to reflect the universal nature of the Qur’an. The primary focus of the concept of naskh-mansukh, which also serves as a determining variable, as proposed by Nasr Hamid, lies in the aspect of context (siyaq). He argues that in determining which verses are naskh and which are mansukh, one should not rely on the chronological order of the verses’ revelation, but must instead consider the contextual analysis of the situation in which the verse was revealed. This is based on the assumption that every verse of the Qur’an was revealed within a socio-cultural context relevant to the needs of society at that time. Therefore, he interprets naskh not as abrogation or revocation, but rather as the replacement (ibdal) of one verse with another, which occurs due to changes in circumstances and conditions that cause the application of that verse to be temporarily suspended until it is reintroduced in accordance with the prevailing conditions.